A streamlined proximity extension assay using POEGMA polymer-coated magnetic beads for enhanced protein detection - Hu, Jiumei; Zhang, Pengfei; Shao, Fangchi; Wang, Tza-Huei (Frontiers in Bioengineering and Biotechnology, 2024)
The detection of protein biomarkers presenting at low concentrations in biological fluids is essential for disease diagnosis and therapeutic monitoring. While magnetic beads-based solidphase immunoassays have shown promise in achieving high sensitivity for detecting lowabundance proteins, existing protocols suffer from limitations such as the cumbersome need for bead blocking and washing steps to minimize adsorption of non-specific biomolecules. These extra requirements lead to increased assay complexity and the risk of procedural errors. In this study, we present a streamlined magnetic proximity extension assay (MagPEA) using poly (oligo (ethylene glycol) methacrylate) (POEGMA)-coated beads. The polymer brush on bead surface, on the one hand, provides an effective mechanism for repelling non-specifically bound biomolecules that contribute to background signal generation without performing any bead blocking and washing steps. On the other hand, it facilitates the immobilization of capture antibodies on bead surface by simply embedding the antibodies onto the porous polymer under vacuum. Using the human inflammatory factor IL-8 as a demonstration, we show that the incorporation of POEGMA beads into MagPEA workflow significantly simplifies assay procedure while maintains high sensitivity.